Dual Model of Marketing and Branding during the pandemic in Indonesia - Ardiansyah, Tedy; Teruna, Dipa (Majalah Ilmiah Bijak, 2022)
The problem in marketing and branding is that it is not easy where in 2021 almost a dozen companies will close which will result in company losses and disrupt the Indonesian economy. This research of the purpose to find out the similarities in the perception in the form of words from each informant regarding marketing and branding strategies, and secondly is to think of something a new model of marketing and branding. The research was carried out employing a qualitative case study approach, where the sample was taken from 5 informants who had validity and credibility. The analysis carried out was assisted by using the Nvivo version 12 tools which led to a cluster analysis to find out the similarities in marketing and branding perceptions as well as an analysis map to bring up a new model of marketing and branding. The findings confirmed the premise, which was based on cluster analysis, that all informants had the same and strong perceptions when it comes to marketing and sales, branding strategies, which is evidenced by the Pearson correlation coefficient between 0.41-0.60. Then Map Analysis for Branding, Map Analysis for Online and Conventional Marketing and Map Analysis for Social Media form a new model in carrying out marketing and branding during the pandemic in Indonesia. The advantage of the model formed is a combination of marketing strategies and branding of informants with one another.